NOD2 drives regenerative fetal-like reprogramming in the intestinal epithelium - Derek K. L. Tsang; Charles Maisonneuve; Arshad Ayyaz; Elisabeth G. Foerster; Marry Nissan; Lauren Baerg; Daniel Trcka; Bibaswan Ghoshal; Boyan K. Tsankov; Giuliano Bayer; Madison Denney; Catherine J. Streutker; et al. (Proceedings of the National Academy of Sciences, 2026)
Inflammatory injury to the intestine triggers a reprogramming of the intestinal epithelium to a fetal-like state that drives rapid restoration of the epithelial barrier. Although the intestinal microbiota is a key modulator of inflammation, its role in influencing epithelial fetal-like stem cell reprogramming and consequent restitution remains unclear. Using irradiation (IR) injury as a model for small intestinal epithelium injury and repair, we found that the intestinal microbiota accelerated epithelial restitution by amplifying a repair-associated inflammatory response that promoted the emergence of fetal-like intestinal epithelial cells (IECs), marked by Ly6a and Clu . NOD2 , the strongest genetic link to the development of Crohn’s disease, was found to be expressed in fetal-like IECs following injury. Employing an ileal organoid model, we demonstrated that NOD2 activation by its peptidoglycan ligand potentiated an inflammatory gene signature characterized by interferon signaling, concurrent with enterocyte recovery. NOD2 deficiency exacerbated epithelial apoptosis following IR injury, whereas epithelial-specific NOD2 signaling promoted fetal-like IEC emergence and increased epithelial proliferation. Collectively, these findings reveal a pivotal role for the microbiota and NOD2-mediated microbial sensing in regulating fetal-like IEC fate after injury, thus contributing to the protective function of this microbial sensor during intestinal inflammation.